Peningkatan Kinerja Guru Dalam Menyusun Perangkat Pembelajaran Melalui Supervisi Akademik - S Iskandar (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2019)
Many problems of teacher performance are: the implementation of learning does not go according to plan; and the performance of teachers in planning learning is still in the predicate enough and low. Subjects in this study are the teachers of SMK Negeri 1 Abung Selatan. The research method used was School Action Research. Based on the results obtained, it can be concluded that the performance of teachers in planning learning increases significantly through optimization of academic supervision with group and individual techniques. This is based on the findings: The increase in the completeness of documents occurred from 50%, 88%, and 94%. PTS plans to increase by 90%, thus the indicator of success in completeness of the document has been reached and the cycle is stopped; and The four predicate performance appraisals in the first cycle, the distribution of the predicate is: Not good enough 0%, good enough 42%, good 58% and very good 0%. In cycle II, the predicate distribution is: Not good enough 0%, good enough 8, good 42% and very good 49. Good and Very Good Predicate is 42 + 49 = 91%. Thus, it can be said that there has been an increase in the distribution of the predicate performance of Prasiklus to Cycle I.